2009
DOI: 10.18512/1980-6477/rbms.v8n2p117-130
|View full text |Cite
|
Sign up to set email alerts
|

Damage of the Spittlebug Deois flavopicta (Stal) (Hemiptera: Cercopidae) to Maize in Intercropping System With Brachiaria Grass

Abstract: One of the possibilities of recovering degraded areas intended for cattle raising is the maize-Brachiaria spp. integration. In this system, it recovers soil fertility through the correct use of lime and adequate fertilizer replacement. The plantation of the two agricultural explorations is made simultaneously. However, the presence of some of these insects is the spittlebug, (Hemiptera: Cercopidae), a sucking insect causing damage to the pastures both, through nymph and adult feeding. In maize only the adult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…; Holmann and Peck, 2002) and sugarcane (Sacharum officinarum L.; Rossato et al, 2019). Also are occasional pests of maize (Zea mays L.) and rice (Oryza sativa L.) (Thompson, 2004;Carvalho and Webb, 2005;Cruz et al, 2009;Heinrichs and Muniappan, 2017). These xylem-feeders have several common names in different countries as follow: spittlebugs (United States of America), froghoppers (Australia and United Kingdom), salivazo or mion (Colombia), salivita (Cuba and Nicaragua), baba de culebra (Central America), candelilla (Venezuela), mosca pinta (Mexico) and cigarrinhas (Brasil).…”
Section: Introductionmentioning
confidence: 99%
“…; Holmann and Peck, 2002) and sugarcane (Sacharum officinarum L.; Rossato et al, 2019). Also are occasional pests of maize (Zea mays L.) and rice (Oryza sativa L.) (Thompson, 2004;Carvalho and Webb, 2005;Cruz et al, 2009;Heinrichs and Muniappan, 2017). These xylem-feeders have several common names in different countries as follow: spittlebugs (United States of America), froghoppers (Australia and United Kingdom), salivazo or mion (Colombia), salivita (Cuba and Nicaragua), baba de culebra (Central America), candelilla (Venezuela), mosca pinta (Mexico) and cigarrinhas (Brasil).…”
Section: Introductionmentioning
confidence: 99%
“…Although the tactic of intercropping maize with brachiaria has been implemented for decades, the body of literature concerning the influence of this intercropping system on pests of maize is limited. What is known from this scant literature is that intercropping maize with brachiaria can engender a reduction in the damage caused by secondary pests, such as the spittlebug Deois flavopicta (Stal), and that Spodoptera frugiperda larvae can survive when feeding solely on brachiaria 18,19 . By contrast, stem borers such as Chillo partellus (Swinhoe) are highly attracted to brachiaria despite its larvae not being able to survive on this grass 20 .…”
Section: Introductionmentioning
confidence: 99%
“…What is known from this scant literature is that intercropping maize with brachiaria can engender a reduction in the damage caused by secondary pests, such as the spittlebug Deois flavopicta (Stal), and that Spodoptera frugiperda larvae can survive when feeding solely on brachiaria. 18,19 By contrast, stem borers such as Chillo partellus (Swinhoe) are highly attracted to brachiaria despite its larvae not being able to survive on this grass. 20 As for other sap suckers, a recent study has shown that adults of the leafhopper Dalbulus maidis, an emerging key pest in Brazil, can survive for 2-3 months on brachiaria in the absence of maize plants in the field (i.e.…”
Section: Introductionmentioning
confidence: 99%